The Diagnosis as “Soft” Technology: a Proposal to Assess the Viability of Knowledge Management in Hotel Tourism Organizations - Franch Leon, Katia; Cabreja Piedras, Saray (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
A mid-twentieth century, the global economic environment has changed the ways of seeing organizations; the tangible elements of the industrial era left behind as sources of value creation for business. There are new guidelines for corporate governance; forming new type organizations where resources can create and increase the value of companies are being intangible precisely today. Of particular importance in this context acquires knowledge and management, hence the efforts made by the organizations implementing knowledge management as a new approach, however, many projects fail for not having previously studied the existing objective and subjective conditions, which They can be viable or hinder the shares comprising a project like this. Hence the importance that the diagnosis in this attempt, the power to answer questions like What do I need? What I tell? How I can give solution? Accordingly, the article proposes a methodology to assess the viability of knowledge management in hotel tourism entities within the group considering technology or tool "soft" that can have both researchers and consultants who want to collaborate with companies in that endeavor.